Kondisi Pendahulu dan Gejala Groupthink dalam Dinamika Komunikasi Politik - Lisa Adhrianti (Jurnal Communicate, 2016)
Groupthink phenomenon in the context of political communication in the scope of the legislative group in the Indonesian parliament where members of multipar pol heteroge11eous background, but often resulted in cont roversial decisionsand unpopular. The paradigm of this research is postpositivis with a qualitativeapproach. Methods used in this research is a case study. In general, this studycm firmed that groupthink occurs in tire dynamics of political communication in the legislatiPe drnft law K I P group WL1rking Committee of Representatives Commission I 011 a process t:f discussion a11d decision-making of public bodies. Tlzere are se<'eral Ct JJ t dititms predecessor (antecedent) which prod uces some symptoms of grouptlti11k hallmark t{t!ze Indonesian parliament, namel y that the cohesion of the group is not /1ased on the fear factor or the reluctance of the figure of leaders in ilze group, lnt t lwcnuse of the presu re (:f time for completionof tasks, fatigue and co1 (lict of intereM s <uith the group executive, which thenforces the legislatiPe group to produce n decision that can not be said to be either through a compromise measure tlta t succeeded in presenti11g a new article, namel!tl.J, 15, and 16 in tile drntt laze KIP :!OOS .